PELAYANAN PUBLIK PADA ERA NEW NORMAL DI SAMSAT KABUPATEN MINAHASA UTARA - Michael Octavianus Gad Langelo; Maria H. Pratiknjo; Leviane J. H. Lotulung (AGRI-SOSIOEKONOMI, 2021)
This study aims to analyze the Public Service in the Era of New Normal in Samsat of North Minahasa Regency. This research design is a qualitative descriptive study that aims to present data systematically, factually and accurately about the facts that occur in the field. This research is more emphasized on data obtained from research subjects. The data sources of this research are divided into two types, namely primary data and secondary data collected by interview, observation, and document techniques. Interviews were conducted on 10 informants. The data analysis technique used in this research is qualitative analysis. The results showed that public services in the Era of New Normal in Samsat of North Minahasa Regency on each indicator of responsiveness, responsibility and accountability had been carried out properly in accordance with the SOPs and basic references that had been set.